Understanding Smartwatch Adoption in a Developing Economy: An Extended Technology Acceptance Model (TAM) Perspective - Md. Al Mamun; Md. Chhali Uddin; Shayla Khanom; Abu Daud Mahir; Radoan Islam (International Journal of Entrepreneurship, Business, and Creative Economy, 2026)
This study examines the factors that influence the adoption and purchase intention of smartwatches among people in Bangladesh by adding additional factors to the Technology Acceptance Model (TAM). The research tests a sequential model using data from 406 respondents, in which technological and social factors affect intention to use, which in turn affects purchase intention, using PLS-SEM. The results suggest that social influence is the most important predictor of intention to use, followed by perceived usefulness and perceived visibility (which has effects similar to perceived usefulness), and then perceived ease of use (which is not significant). Intention to use is a significant predictor of purchase intention, and perceived affordability has a positive relationship with purchase intention. An important contribution is the explicit separation between intention to use and purchase intention, reflecting the difference between attitudes towards the technology and the actual purchase of the technology, especially in price-sensitive developing economies. The results provide concrete pointers for the communicative interaction between marketers and manufacturers in order to convey functional value, social influence, and a flexible pricing policy. The study provides empirical evidence on the adoption of wearable technology in the underexplored economies of the developing world.